2016
DOI: 10.1152/japplphysiol.00859.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventilatory variability and complexity in patients with hyperventilation disorder

Abstract: It has been hypothesized that hyperventilation disorders could be characterized by an abnormal ventilatory control leading to enhanced variability of resting ventilation. The variability of tidal volume (VT) often depicts a nonnormal distribution that can be described by the negative slope characterizing augmented breaths formed by the relationship between the probability density distribution of VT and VT on a log-log scale. The objectives of this study were to describe the variability of resting ventilation [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Many individuals with 'idiopathic' or unexplained breathlessness are now recognized to have irregularities in the pattern and control of their breathing, both at rest and during exercise. 20,21 Historically, individuals with this clinical presentation were described as chronically 'hyperventilating'. Defining and characterising this abnormality, based on the presence of systemic hypocapnia, has however proven difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many individuals with 'idiopathic' or unexplained breathlessness are now recognized to have irregularities in the pattern and control of their breathing, both at rest and during exercise. 20,21 Historically, individuals with this clinical presentation were described as chronically 'hyperventilating'. Defining and characterising this abnormality, based on the presence of systemic hypocapnia, has however proven difficult.…”
Section: Discussionmentioning
confidence: 99%
“…24 Accordingly, more recent work has focussed on detecting irregularities in breathing pattern. 2,6,20 Such breathing pattern irregularities appear to be ubiquitous in those with idiopathic breathlessness or hyperventilation 20,25 yet new, readily-accessible, objective techniques are needed to quantify these breathing pattern abnormalities. Caldirola and colleagues 15 utilised the mathematical approach of ApEn analysis to evaluate ventilatory indices acquired from resting breath-by-breath data, to successfully quantify increased ventilatory irregularity in a cohort of individuals with anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in a multivariate analysis, the sensory‐affective domain of dyspnoea was associated with the depression trait, accordingly with our initial hypothesis. VT demonstrates some physiological variability, any deviation, that is reduction or augmentation, could promote dyspnoea sensation. Interestingly, we further showed that the decreased variability of VT was associated with the sensory‐affective domain of dyspnoea in PE.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to measure breathing pattern by assessing changes in amplitude and frequency of tidal volume using several techniques (e.g. optical electronic plethysmography and manual assessment of respiratory motion).…”
Section: Introductionmentioning
confidence: 99%